Association Between Lipid Accumulation Product and Cognitive Function in Hypertensive Patients With Normal Weight: Insight From the China H-type Hypertension Registry Study - Xie, Yanyou; Li, Junpei; Yu, Guotao; Zhou, Xinlei; Zhou, Wei; Zhu, Lingjuan; Wang, Tao; Huang, Xiao; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Neurology, 2022)
Background Hypertension is a major cardiovascular risk factor for cognitive impairment. Lipid accumulation product (LAP), an index that represents fat overaccumulation in the body, has been shown to be associated with cardiovascular disease. Nevertheless, the relationship between LAP and cognitive function in hypertensive patients with normal weight has been infrequently studied. Objective This study aimed to assess the relationship between LAP and cognitive function in hypertensive patients with normal weight. Methods This study included 5,542 Chinese hypertensive patients with normal weight. Cognitive function was evaluated using the Mini-Mental State Examination (MMSE). The relationship between LAP and MMSE scores was evaluated using multiple linear regression. Results The mean age of the participants was 64.8 ± 9.3 years, and 2,700 were men (48.7%). The mean MMSE score was 24.5 ± 5.1 in men and 19.2 ± 6.5 in women. The mean LAP was 26.2 ± 25.5 in men and 42.5 ± 34 in women. Log10-LAP showed a significant positive association with MMSE score (men: β = 0.69, 95% CI 0.14–1.24, p = 0.015; women: β = 1.03, 95% CI 0.16–1.90, p = 0.020). When LAP was divided into 3 groups according to tertiles, participants in the third LAP tertile had higher MMSE scores for both men (p for trend = 0.04) and women (p for trend = 0.015). Conclusion LAP showed an independent positive association with MMSE in Chinese hypertensive patients with normal weight.